Boosting the Raman signal on a semiconductor-nanotube membrane for reporting photocatalytic reactions on site. Issue 71 (6th August 2020) - Yang, Lingling; Zhao, Chenxi; Xu, Jingwen; Guo, Junli; Gao, Zhida; Song, Yan-Yan
Abstract : Smooth TiO2 -nanotube arrays are effective in reducing Raman-scattering loss in porous structures, and thus promising in monitoring photocatalytic reactions on site. Abstract : A smooth TiO2 nanotube-based membrane (S-TiNM) is demonstrated to be effective in reducing the Raman-scattering loss in 3D porous structures. Using the photocatalytic reduction of 4-nitrothiophenol as a model, the S-TiNMs show promising potential as sensitive SERS substrates to investigate photocatalytic reactions on site.